REASONS FOR DELAYED PRESENTATION OF PATIENTS WITH ST SEGMENT ELEVATION MYOCARDIAL INFARCTION TO THROMBOLYTIC THERAPY IN CARDIOLOGY DEPARTMENT OF AYUB TEACHING HOSPITAL ABBOTTABAD - Samin, Ariz; Mehwish Taqueer; Mahnoor Javaid; Zoya Fayaz; Noor ul Huda; Nayha Nadeem; Rida Fatima Saeed; Ayesha Laraib (Journal of Ayub Medical College Abbottabad, 2021)
Background: ST elevation myocardial infarction (STEMI) is one of the leading causes of morbidity and mortality. Any delay in reperfusion therapy is associated with poor outcomes. This study was done to know the major reasons for delayed presentation to thrombolytic therapy. Methods: This cross-sectional study was conducted at the Coronary Care Unit (CCU) of Ayub Teaching Hospital, Abbottabad from March 2019 till June 2020. A total of 120 diagnosed STEMI patients late for thrombolysis therapy and admitted in the CCU were included in this study. Non-probability convenience sampling technique was used. Data was analysed using SPSS version 16.0. Results: The mean age of the patients was 61.6±1.07 years. Most of them were married (111), unemployed (85) and lived in urban areas (69). The most important reasons for delayed presentation of STEMI patients to thrombolytic therapy were due to the attribution of symptoms by patients to other conditions/diseases (57.5% CI:48.53-66.47), attempted self-treatment (50.8% CI: 41.76-59.91), misdiagnosis of symptoms (50%, CI:40.92-59.08), living in an area far away from any hospital (45%, CI:35.48-53.60) and problems of transportation (37%, CI:28.17-45.78). Conclusion: The early arrival of patients to health care facility in time is critical in diseases like STEMI. There can be many reasons for delayed presentation of patients to thrombolytic therapy but the most important ones were attribution of symptoms by patients to other diseases, attempted self-treatment, misdiagnosis of symptoms, and problems of transportation.